A Critical Study of Startup Financing Dynamics and Emerging Approach to Attracting Capital Resources - Mohd Akhlak Hussain (Journal of Corporate Finance Management and Banking System, 2024)
This study delves into the diverse landscape of startup financing in India, examining the sources of funds and emerging approaches to attracting capital resources. Through an analysis of general statistics, including the types of startups, gender distribution of founders, and funding sources, the study provides insights into the dynamics of the startup ecosystem. The findings reveal that a significant portion of startups rely on internal sources such as family and friends, personal savings, and bootstrapping, while external sources like angel investors, venture capitalists, and government grants also play a crucial role. Additionally, the study explores various financing options available to startups at different stages of their lifecycle, including debt financing, commercial lenders, government programs, and leasing arrangements. By shedding light on these financing avenues, the study aims to inform entrepreneurs, investors, and policymakers about the evolving landscape of startup finance and facilitate informed decision-making.